Edukasi HACCP Pada UMKM CV. Pawon Ibun Dalam Meningkatkan Daya Saing Industri Global - Awanda Winar Fitriana; Yulistiani, Ratna; Fauziyah, Nur Aini; Misbach, Moch. Harits Pradana (Universitas Nahdlatul Ulama Sidoarjo, 2024)
Education on HACCP conducted at CV. Pawon Ibun Tuban, East Java aims to provide basic capital in the implementation of HACCP. The activity was carried out from August to November with several stages of implementation. The methodology of implementing this training activity is by using a qualitative analysis in the form of a quiz given to CV. Pawon Ibun employees to measure the success rate of education that has been conducted. The steps taken to facilitate the implementation of educational activities on HACCP start from the preparation stage, implementation stage, evaluation stage and mentoring stage. The results of the methodology stages carried out in the form of questionnaire are the need for assistance in the intensive implementation of HACCP because there are several aspects that still need to be improved.